Genetic analysis of resistance to fusarium root rot in common bean - Mukankusi, Clare Mugisha; Derera, J.; Melis, R; Gibson, PT; Buruchara, Robin Arani (Springer, 2011)
Fusarium root rot (FRR) is a major disease of common bean worldwide. Knowledge of the inheritance of resistance to FRR would be important in devising strategies to breed resistant varieties. Therefore, a 12 × 12 full diallel mating scheme with reciprocal crosses was performed to generate 132 F1 progenies, which were then advanced to the F3. The progenies were evaluated for resistance to FRR under green house conditions in Uganda. General combining ability (GCA) effects were highly significant (P ? 0.01) for disease scores. Specific combining ability effects were not significant (P > 0.05) in the F1, but were highly significant (P < 0.01) in the F3 generation. These results indicate that resistance to FRR was governed by genes with additive effects in combination with genes with non-additive effects. Reciprocal differences were also significant (P = 0.01) at F1 and F3, primarily reflecting a large influence of maternal effects in both these generations. In fact, susceptible parents did not differ significantly (P > 0.05) for disease scores when used as paternal parents in the F3, but differed strongly as maternal parents (P = 0.0002). Generally, the progenies were distinctly more resistant when the resistant parent was used as the female in crosses, especially as observed in the F3. The maternal effects were strong in the F3 generation, suggesting a complex form of cytoplasmic–genetic interaction. The non-maternal reciprocal effects in the F3 were significant (P < 0.05) in both the resistant × resistant diallel, and in the resistant × susceptible crosses. Mid-parent heterosis (MPH) occurred in most crosses, with average heterosis approximately equal in each of the three generations, indicating that epistasis was probably more influential than dominance of individual genes. Gene-number formulas indicated that several genes were involved in resistant × susceptible crosses. Among resistant × resistant crosses, many produced continuous distributions of F1 progeny scores, suggesting polygenic inheritance, while bi-modal distributions were characteristic of the F3 distributions, and fit expected ratios for two or three loci segregating in each cross. Dominant forms of epistasis favoring resistance were strongly indicated. Parent–offspring heritability estimates were moderate. Overall, the results indicate that resistant parents contain a number of different resistance genes that can be combined with the expectation of producing strong and durable resistance. The lines MLB-49-89A, MLB-48-89, RWR719 and Vuninkingi, with large and negative GCA effects, contributed high levels of resistance in crosses and would be recommended for use in breeding programs.